2008
DOI: 10.3181/0710-rm-266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3,5-Diiodo-L-Thyronine Administration on the Liver of High Fat Diet-Fed Rats

Abstract: In rats fed a high fat diet (HFD), long-term administration of 3,5-diiodo-L-thyronine (T2), a naturally occurring iodothyronine, was shown to reduce body-weight gain, fat mass, and hepatic lipid accumulation. This work was aimed at investigating the mechanisms of T2 action in the liver of HFD rats. The results show that HFD induces liver lipid peroxidation and stimulates the activity of enzymes involved in hydrogen peroxide (H2O2) metabolism, catalase in particular. Moreover, quantitative RT-PCR revealed HFD-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 45 publications
3
41
1
Order By: Relevance
“…Also T 2 , as T 3 , is able to stimulate both resting metabolic rate and mitochondrial activity in hypothyroid rats (Moreno et al 1997). Moreover, when administered to rats receiving a high-fat diet, T 2 was able to both prevent (Lanni et al 2005, Grasselli et al 2008 and reduce (Mollica et al 2009) the development of liver steatosis. Once entering the cell, THs mostly bind to specific nuclear receptors (TRs) acting as ligand-dependent transcription factors ('receptor-mediated' effects).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Also T 2 , as T 3 , is able to stimulate both resting metabolic rate and mitochondrial activity in hypothyroid rats (Moreno et al 1997). Moreover, when administered to rats receiving a high-fat diet, T 2 was able to both prevent (Lanni et al 2005, Grasselli et al 2008 and reduce (Mollica et al 2009) the development of liver steatosis. Once entering the cell, THs mostly bind to specific nuclear receptors (TRs) acting as ligand-dependent transcription factors ('receptor-mediated' effects).…”
Section: Introductionmentioning
confidence: 94%
“…The anti-steatosic effects of iodothyronines observed in vivo (Lanni et al 2005, Grasselli et al 2008 could not distinguish between their direct effects on the liver and the secondary effects due to upstream changes in endocrine or metabolic pathways. Subsequent in vitro experiments using primary rat hepatocytes overloaded with lipids demonstrated that T 2 and T 3 were able to directly reduce the excess fat (Grasselli et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First strand cDNA was synthesized from 1 μg of total RNA (24). Quantitative RT-PCR was performed in quadruplicate in a final volume of 25 μl containing 0.3 μM of each primer, 10 ng cDNA, 1x SybrGreen PCR Master Mix and were analyzed in 96-well optical reaction by 7900 HT fast real-time PCR system (Applied Biosystems, Monza, Italy).…”
Section: Rna Extraction and Real-time Rt-pcrmentioning
confidence: 99%